Phylogenetic analysis of cyrtocrinid crinoids and its influence on traditional classifications - Romano, Marco; Manni, Riccardo; Nicosia, Umberto (Journal of Mediterranean Earth Sciences, 2016)
The cyrtocrinids are a group of mostly Mesozoic articulated crinoids, with rare Cenozoic forms and only two extant taxa. A careful analysis of previous studies indicates that the systematic arrangement of cyrtocrinids is very weak and unsatisfactory for several reasons. In particular, most of the original descriptions and diagnosis date from the past century and are logically influenced by a classical typological philosophy. Not being based on phylogeny, the currently accepted groups for cyrtocrinids must be putatively regarded as “artificial”. In addition, an inappropriate use of characters has been used, typically considered as diagnostic in other groups of crinoids but only marginally applicable to cyrtocrinids (the latter differently characterized for several highly distinctive and autapomorphic characters). In order to mitigate these problems and to arrive at the definition of characters and clades based on unambiguous synapomorphies, we present in this paper a preliminary and exploratory phylogenetic analysis based on parsimony of cyrtocrinids. The obtained topology showed how the traditionally recognized groups prove to be highly paraphyletic and polyphyletic, indicating the need for a complete revision of cyrtocrinids taxonomy, based on phylogeny. The gap-weighting method used for codifying morphometric continuous character, has proved to be a powerful tool to obtain well-resolved and consistent cladograms, even with a limited number of characters.